(untitled) (Journal of Governance and Development (JGD), 2016)
Decentralization is the devolution of authority from central to local government to manage the domestic affairs based on the needs and aspirations of its people. Decentralization process also translates into providing autonomy to the local government. However, the degree of autonomy granted to local governments raises a dilemma due to political pressure and political demands. Too much autonomy can sometimes lead to a disproportionately distribution of power in the hands of the elites. This paper, therefore, attempts to critically analyze the practice of decentralized autonomy in local governments in Indonesia. Specifically, it argues that the current practice of decentralization and local autonomy inhibits the ability of the local government to effectively empower greater participation from citizens. Instead, poor local citizens continue to be sidelined in the fight for political control.